Research progress of rhizosphere microorganisms in Fritillaria L. medicinal plants - Zhou, Nong; Mei, Chun-Mei; Zhu, Xing-Yu; Zhao, Jing-Jing; Ma, Ming-Guo; Li, Wei-Dong (Frontiers in Bioengineering and Biotechnology, 2022)
The soil’s rhizosphere is a highly active place where the exchange of substances and information occurs among plants, soils, and microorganisms. The microorganisms involved are crucial to the activities of plant growth and development, metabolism, and reproduction. Fritillaria L. medicinal plants are unique Chinese medicinal ingredients, but the continuous cropping obstacles formed in the artificial planting process is severely harmful to the growth and development of these medicinal plants. In this review, we summarized the current species and distribution of Fritillaria L. in China, and analyzed the changes in microbial diversity (mainly among bacteria and fungi) in the rhizosphere of these plants under long-term continuous cropping. The fungi showed an increasing trend in the soil rhizosphere, resulting in the transition of the soil from the high-fertility “bacterial type” to the low-fertility “fungal type” as planting years increased. Furthermore, the interaction between Fritillaria L. medicinal plants and the rhizosphere microorganisms was reviewed, and promising applications for the rhizosphere microbiome in the cultivation of Fritillaria L. medicinal plants were suggested. It is expected that this review will facilitate the in-depth understanding of rhizosphere microorganisms in the growth, accumulation of active ingredients, and disease control of Fritillaria L.